Notes on contributors - Haron, Razali (IIUM Press, 2019)
For this Al-Shajarah Special Issue, the Islamic Banking and Finance takes the front by focussing on Islamic social finance (ISF) issues. ISF issues are rapidly gaining the attentions of all players in the field and Al-Shajarah plays its part in presenting several selected related issues, highlighting the challenges and recommending possible remedies and solutions based on either empirical evidences or analyses of current scenarios and best practices. Among the issues discussed are zakāt contributions, the impact of financial crimes on performance of firms, ISF and the imperative for social impact measurement, the value-based intermediation approach on ISF, the potential in reviving waqf through crowd-funding technology, crypto-currency, zakāt distribution on social welfare, Islamic fintech investment innovation, the role of ISF and the insurance practices which can be resolved by introducing takāful in India.